Gastric cancer diagnosis and treatment - Siewert, J. R.; Kelsen, D.; Maruyama, K. (Berlin : Springer, 2000)
It covers all the aspects of the management of gastric cancer
Title from disc label
An interactive training program
System requirements: Pentium processor based personal computer, Microsoft Windows 95/98/2000 or Windows NT 4.0 with Service Pack 3 or later, 8 MB RAM for Windows 95/98/2000 (16 MB recommended), for Windows NT 16 MB RAM (24 MB recommended), CD-ROM drive 4x speed, VGA-card (800 x 600) and True color
Keywords: Stomach Neoplasms -- diagnosis; Gastrointestinal Neoplasms